Jedność wielości = Unity and Multiplicity - Wnuk-Lisowska, Elżbieta (Studia religiologica, 2012)
Philosophical discourse in Islam revolves around God, and God’s manifestation in the world. This article attempts to describe the philosophical concept, and especially the Sufi concept, of God. For Muslim philosophers the question “how does unity give rise to multiplicity?”had a crucial meaning. In Islam God is One, and everything else is two or more. The Oneness of being remains inaccessible to people. However, Sufi s tried to give an answer to the question “What is Reality? What is the ‘face of God’, and what does this notion really mean?”And also “what veils separate Him from His creation?”Sufi s tried to find the answer to all these questions not in the calm of a library but in deep religious experience. Because God in His mercy revealed the Laws in order that people would be able to make choices which lead directly to their felicity in the next stage of their experience. This was a difficult and dangerous process, and it required from neophytes a love of God. In their searches, the Sufi s try to answer the question of what one sees when one throws off the inhibiting shackles of the mind and senses, what does one feel when one crosses the border of the phenomenal world? What kind of world does one observe when one wakes up from a dream which is life? What does one see in the state of illumination?